Umbrella action research projects as a mechanism for learning and teaching quality enhancement. Issue 6 (19th September 2019) - Kember, David; Douglas, Tracy; Muir, Tracey; Salter, Susan
ABSTRACT: Umbrella action research projects link together a number of small action research projects under a common organizational and thematic umbrella. This article provides an example of an umbrella action research project, which aimed for teaching quality enhancement. There are two mechanisms by which teaching quality can be enhanced. The first of these is through the improvements initiated in the small projects, which are normally conducted by teachers in the courses they teach. The second mechanism is that of the collective reflective discussions of the whole project team. The collective umbrella that over-arches the individual projects provides a mechanism for participants to collectively transform their understanding of the common thematic issue. There is, therefore, the possibility of an emancipatory transformation, so that the whole achieves more than the sum of the individual projects. This article substantiates the impact of umbrella action research projects by presenting case studies from an overall project that focused on online learning. The cases highlight our reflective discussions on promoting student engagement in online learning. They show how our collective understanding of engagement in online learning was advanced and some of the means tried in the small projects to encourage student engagement. As there is evidence of teaching quality enhancement through the umbrella action research project, we discuss the possibility of redirecting some of the resources currently devoted to quality assurance to quality enhancement through encouraging action research projects.